Interaction between biological and chemistry fungicides and tomato pollinators - Silva-Neto, Carlos de Melo e; Ribeiro, Anna Clara Chaves; Gomes, Flaviana Lima; Neves, Jordana Guimarães; Melo, Aniela Pilar Campos de; Calil, Francine Neves; Nascimento, Abadia dos Reis; Franceschinelli, Edivani Villaron (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
The use of agrochemicals is harmful to bees visiting agricultural crops, reducing production gains from pollination, but the effect of fungicides on these bees is not known. The objective of this study was to verify the effect of bee visitation influenced by different fungicides on the tomato crop and on the deposition of pollen grains on the stigma, number of seeds, mass and fruit size. The experiment was conducted with 10 treatments: (T1) control treatment, without application of agrochemicals; (T2 and T3) Bacillus subtilis in different application frequencies; (T4) copper hydroxide; (T5) B. subtilis and copper hydroxide; (T6) acibenzolar-S-methyl; (T7) (trifloxystrobin+tebuconazole) and B. subtilis; (T8) copper hydroxide+Mancozeb; (T9) propineb+(trifloxystrobin+ tebuconazole); (T10) (trifloxystrobin+tebuconazole)+B. subtilis+copper hydroxide. The presence of the pollination mark on the flower, the pollen load of the stigmas, the number of seeds per fruit, and the size and mass of the fruits were determined in each treatment. Subsequently, the mortality rate of Melipona quadrifasciata (Hymenoptera, Apidae) exposed to four fungicides (trifloxystrobin+tebuconazole; manganese and zinc; copper hydroxide; Bacillus subtilis) was estimated. The mortality rate of M. quadrifasciata over 24 h of evaluation was higher in the treatments with copper hydroxide and trifloxystrobin+tebuconazole (75 and 50%, respectively). The mortality rate was lower in the treatments with manganese and zinc and Bacillus subtilis and in the control treatment. The treatments with trifloxystrobin+tebuconazole reduced the presence of bite marks on the flowers and of pollen grains on the flower stigma. The fruits of the control treatments and treatments with B. subtilis and copper hydroxide were larger and had greater mass, as compared to other agrochemicals. Thus, a higher number of pesticide applications on the tomatoes reduced bee visitation rates to the flowers and, consequently, reduced the amount of pollen grains deposited on the stigmas, also reducing the fruit production.